JURNAL ANALISIS KEPUASAN PELANGGAN MENGGUNAKAN PENDEKATAN IMPROVEMENT GAP ANALYSIS DAN CUSTOMER SATISFACTION INDEX STUDI KASUS PADA KANTOR POS PROCESSING CENTER GRESIK - YAHYA RACHMADANY (Universitas Muhammadiyah Gresik, 2022)
ABSTRACT PT POS Indonesia or better known as the Post Office is one of the business entities engaged in services, especially correspondence. PT. POS Indonesia is one of the service businesses that is also experiencing intense competition. This increasingly fierce competition can be seen with the increasing number of emerging expeditions and multinational private freight forwarding companies, including DHL, Fed-ex (Federal Express), TNT, JNE, J&T. PT. Pos Indonesia won the 2022 Courier Service Top Brand Award at rank 3. The services offered by competitors are also diverse, thus it will be a distinct feature and advantage for each expedition. This requires the owner or manager of the expedition to create a strategy to be able to compete and be superior to its competitors. This study uses the calculation of the application of the IGA (Improvement Gap Analysis) method and the CSI (Customer Satisfaction Index) method so that the level of consumer satisfaction with the service quality of the Post Office will be known. Based on the results of research that has been carried out at the Gresik Processing Center Post Office, the value of the level of customer satisfaction with the Gresik Processing Center Post Office service is 78.10%, which means that customers feel